IMPLEMENTASI PENGUATAN PROFIL PELAJAR PANCASILA DAN RAHMATAL LIL’ALAMIN (P5RA) PADA DIMENSI BERKEBINEKAAN GLOBAL DI MA NU 01 BANYUPUTIH BATANG - Endon Nurcahyati; Noor Miyono; Rasiman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT: Endon Nurcahyati, 2025. Implementation of Strengthening the Student Profile of Pancasila and Rahmatal Lil Alamin (P5RA) on the Global Diversity Dimension at MA NU 01 Banyuputih Batang. Thesis. Supervisors: Dr. Noor Miyono, M.Si; Dr. Rasiman, M.Pd. This study aims to examine the implementation of Strengthening the Student Profile of Pancasila and Rahmatal Lil Alamin (P5RA) in the Global Diversity Dimension at MA NU 01 Banyuputih Batang. The research focuses on: 1) planning the implementation, 2) execution, and 3) evaluation of strengthening the student profile in this dimension. A qualitative approach was employed, utilizing observation, interviews, and documentation for data collection. Informants were purposively selected, including the school principal, teachers, and students actively involved in planning, implementation, and evaluation activities. Data analysis utilized the interactive model of Miles, Huberman, and Saldana, which includes data collection, condensation, display, and conclusion drawing. The findings reveal that: Planning involves identifying needs, developing activity plans, forming teams, and budgeting. Implementation includes intracurricular, co-curricular, extracurricular, and cultural activities. Success indicators encompass cultural appreciation, cross-cultural interaction, reflection, responsibility, and social justice, reflected in school. Keywords: Implementation, Pancasila Student Profile, Rahnmatal lil Alamin, Character Education, Global Diversity, Madrasah Aliyah